Pengembangan Bahan Ajar Modul Berbasis Etnomatematika pada Materi Teorema Pythagoras di Kelas VIII SMP Negeri 06 Tabulahan - Hapri Duwi Putra; Khadijah; Inayanti Fatwa (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2025)
This research is R&D (Research and Development) that aims to 1) determine the characteristics of ethnomathematics-based modules on the Pythagorean Theorem sub-material for class VIII of SMP Negeri 06 Tabulahan. 2) To determine the feasibility of ethnomathematics-based module teaching materials on the Pythagorean Theorem material as a learning resource for class VIII of SMP Negeri 06 Tabulahan. The data collection technique used in this study was a non-test technique, namely questionnaires and documentation. The aspects of feasibility include aspects of content feasibility components, aspects of language components, aspects of presentation components, and aspects of graphic components. The data analysis technique used is the Likert Scale. The results of the study show that 1) The Pythagorean Theorem Module based on Ethnomathematics that was developed has the characteristics of Ethnomathematics. 2) The Ethnomathematics-based module on the Pythagorean Theorem material is Feasible for use as a learning resource for class VIII of SMP Negeri 06 Tabulahan.